DINAMIKA PERKEMBANGAN METODE PENETAPAN HUKUM NAHDLATUL ULAMA DAN MAJELIS ULAMA INDONESIA DALAM PEMBARUAN HUKUM ISLAM - Imam Syafi'i; Lukman Hakim (Program Studi Hukum Keluarga Islam, Fakultas Syariah, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2024)
This research aims to analyze the dynamics of the legal determination method developed by Nahdlatul Ulama (NU) and the Majelis Ulama Indonesia (MUI) in the context of legal reform so that it can accommodate problems that occur in the reality of human civilization. This research is library research, with an Islamic legal approach, qualitative data analysis and documentation techniques from both primary and secondary sources related to the legal determination method (istinbath al-ahkam) developed by NU and MUI. NU's method of legal determination has developed and has become the basic foundation of the legal system, namely using the qauliy, ilhaqiy and manhajiy school of thought approaches and gradually NU has made syarah (explanation) of this system. The MUI perfected the system and mechanism for determining laws using the al-jam'u wa at-taufiq method, the muqaranah method and the bayani and ta'lili methods as an explanation of the manhaji method. Furthermore, the MUI refined and confirmed this method to become organizational regulations. These dynamics reinforce that NU and MUI have moderate and adaptive principles, where Islamic law is flexible, elastic and dynamic according to current developments